New direction of warehousing of tails of concentrating factories - Awdochin, W. M.; Rafijenko, W. A.; Pawłowa, E. P. (Studia Ecologiae et Bioethicae, 2005)
In the given work the new approach to warehousing tails of concentraiting factories reduction of the areas of warehousing, and also improvement of ecological conditions of the location chwostochraniliszcz factories is stated. It is offered to refuse from working chwostochraniliszcz borrowing the big territories and to realize the technological circuit of warehousing of tails in a waste heap.